2019
DOI: 10.1080/1828051x.2019.1606676
|View full text |Cite
|
Sign up to set email alerts
|

Hemogasometry, metabolic profile and acute-phase proteins in primiparous Holstein cows supplemented with butafosfana associated or not of cyanocobalamin

Abstract: The aim of study was to evaluate whether butafosfan, associated or not with cyanocobalamin, alters the metabolic profile, hemogasometrics and acute phase proteins in recent postpartum dairy cows. Twenty-five cows (n ¼ 25) were selected for study and divided into three groups: Butafosfan (BUT, n ¼ 9); Butafosfan þ Cyanocobalamin (BUTC, n ¼ 9); and Control (CTL, n ¼ 7). Treatments were applied daily from calving until 5 days postpartum. Blood samples for hemogasometry were performed on days 0, 1, 2 and 3, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…In the following reports, butafosfan with or without VB12 combination did not significantly increase phosphorus concentration in the blood of dairy cattle (Rollin et al 2010;Kreipe et al 2011;Pereira et al 2013b;Antunes et al 2019;Scharen et al 2021).…”
Section: Butafosfan (Butaphoshan) and Ibc: Chemistry And Biological I...mentioning
confidence: 74%
See 3 more Smart Citations
“…In the following reports, butafosfan with or without VB12 combination did not significantly increase phosphorus concentration in the blood of dairy cattle (Rollin et al 2010;Kreipe et al 2011;Pereira et al 2013b;Antunes et al 2019;Scharen et al 2021).…”
Section: Butafosfan (Butaphoshan) and Ibc: Chemistry And Biological I...mentioning
confidence: 74%
“…EMEA (1999) reported that the precise mode of action of butafosfan was unknown. Many of the studies suggest that it is acting pharmacologically as a complete molecule rather than supplying phosphorus to the organism because blood phosphorus concentration was not significantly changed after iBC administrations in cattle (Rollin et al 2010;Kreipe et al 2011;Pereira et al 2013b;Antunes et al 2019;Scharen et al 2021). This is in line with the pharmacokinetic data which confirmed that butafosfan was eliminated rapidly and a mean of 77% of butafosfan was recovered in the urine within 12 h (EMEA 2000).…”
Section: Evidences About the Mode Of Action Of Butafosfan As A Single...mentioning
confidence: 77%
See 2 more Smart Citations
“…The results showed that the levels of these two enzymes in the B+C3 group were significantly lower than those of the other Ctrl and treatment groups, demonstrating the role of butaphosphan and cyanocobalamin in the health and function of hepatocytes. Liver health plays an important role in preventing metabolic disorders in ruminants, and other researchers have evaluated the effects of this compound on liver health indicators, such as total bilirubin (Antunes et al., 2019 ; Şahal et al., 2017 ; Temizel et al., 2015 ), AST (Pereira et al., 2013 ; Tabele, 2017 ) and gamma‐glutamyl transferase (Pereira et al., 2013 ). Therefore, the use of butaphosphan and cyanocobalamin plays an effective role in reducing the incidence of metabolic disorders by maintaining and promoting liver health and function.…”
Section: Discussionmentioning
confidence: 99%